Student’s Numeracy on Solving Data and Uncertainty Problems in Term of Self-Efficacy - Thoiffatul Khusnun Nisa'; Rooselyna Ekawati; Ahmad Wachidul Kohar (Program Studi S1 Matematika UNESA, 2023)
Numeraticy is the ability to analyze, interpret information, and find a solution by involving one's mathematical knowledge. Numeracy is known to be influenced by self-efficacy. This study aims to describe students' numeracy in solving data and uncertainty problems in terms of high and low self-efficacy. This study is descriptive research with a qualitative approach was carried out by collecting data from research subjects purposively consisting of three students with high self-efficacy and three students with low self-efficacy. The instruments used included a self-efficacy questionnaire, three data and uncertainty questions, and an interview guide. The data is then analyzed using the numeracy’s sub-indicators. The results showed that in general the numeracy of the group of students with high self-efficacy in solving questions containing data problems and uncertainties was better than the group of students with low self-efficacy. Based on these significant differences, it is recommended for teachers to create a learning climate that can support increased student self-efficacy and numeracy. As well as from the results of the interviews which only focused on parts that were not clear from the student's answers, future researchers should conduct interviews on all of the student’s numeracy in order to obtain more complete research data.